2022
DOI: 10.1007/s10899-022-10111-z
|View full text |Cite
|
Sign up to set email alerts
|

Skin Gambling Contributes to Gambling Problems and Harm After Controlling for Other Forms of Traditional Gambling

Abstract: Esports betting and skin gambling involve betting on the outcomes of video game competitions and/or using virtual currencies for betting. The present study evaluated a conceptual model linking video game involvement, video-game related gambling, traditional gambling, and gambling problems and harm. Data were collected via a cross-sectional online survey with 737 participants aged 18 + who engaged in esports cash betting (n = 576), esports skin betting (n = 184), or skin gambling on games of chance (n = 330). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…At the individual level, some people may also adapt in the future by curtailing their engagement in these novel forms as their novelty and honeymoon effects wane, or if individuals moderate their gambling on these products to reduce the harmful consequences they have experienced. Given the young average age of early adopters on the three novel gambling products, some individuals may age out of risky gambling behaviour [2][3][4][5][6][7]. This maturing out of addictions as young people transition to adult roles and responsibilities and experience psychological maturation has been observed for alcohol and other drug addictions [37][38][39].…”
Section: Evidence For the Adaptation Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…At the individual level, some people may also adapt in the future by curtailing their engagement in these novel forms as their novelty and honeymoon effects wane, or if individuals moderate their gambling on these products to reduce the harmful consequences they have experienced. Given the young average age of early adopters on the three novel gambling products, some individuals may age out of risky gambling behaviour [2][3][4][5][6][7]. This maturing out of addictions as young people transition to adult roles and responsibilities and experience psychological maturation has been observed for alcohol and other drug addictions [37][38][39].…”
Section: Evidence For the Adaptation Effectmentioning
confidence: 99%
“…For example, amongst Australian adults, past-year prevalence is 0.6% for esports betting, 0.6% for fantasy sports betting and 0.3% for skin gambling [1••]. These activities attract mainly young adult males [2][3][4][5][6][7]. Most studies have found positive associations between participation in these activities and higher problem gambling severity, although causal relationships remain unclear [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While participation in these emerging gambling activities is currently rare in general adult populations, participation amongst adolescents and young adults is proportionately much higher (Gambling Commission, 2019;Hing et al, 2021b;Hing et al, 2021;Russell et al, 2020). Early research also shows that esports betting and skin gambling are associated with higher levels of involvement in traditional gambling activities and gambling-related harm, especially for adolescents and young adults (Gainsbury et al, 2017b;Greer et al, 2021Greer et al, , 2022Hing et al, 2021cHing et al, , 2022Wardle, 2019). However, participation in these emerging gambling activities only partially accounts for greater intensity of gambling involvement and harm, suggesting the influence of other underlying factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although loot boxes have received the most attention among researchers and policy makers, the book also explores a variety of other systems, such as social casinos, fantasy sports, skin betting, trading rooms, esports, microtransactions and the symbolics of gambling within gaming products. Notably, skin betting has been found to predict gambling problems and gambling harms, particularly among the youth (Greer et al, 2022; Wardle, 2019). Although betting can occur with in-game currency, Wardle shows how for some consumers these currencies can also hold a value, quite similarly to real-life money.…”
mentioning
confidence: 99%